1997
DOI: 10.1089/acm.1997.3.291
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Intensive Yoga Training on Physiological Changes in 6 Adult Women: A Case Report

Abstract: The short-term effects of 4 weeks of intensive yoga practice on physiological responses in six healthy adult female volunteers were measured using the maximal exercise treadmill test. Yoga practice involved daily morning and evening sessions of 90 minutes each. Pre- and post-yoga exercise performance was compared. Maximal work output (Wmax) for the group increased by 21%, with a significantly reduced level of oxygen consumption per unit work but without a concomitant significant change in heart rate. After int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 6 publications
2
18
1
Order By: Relevance
“…During daily practice of meditation by concentrating, on breathing the basic activity of bulbopontine complex is modified in such a way as to slow down its rhythm by voluntarily prolonging the phases of inspiration and expiration by stretching to Ray et al [14] observed significant improvement in VO 2 max after Yogic training. Raju et al [15] have found a significant increase in oxygen consumption per unit work after yoga training which are similar to our study. Improvement in lung functions as well as cellular machinery explains raised VO 2 max after regular practice of meditation.…”
Section: Discussionsupporting
confidence: 92%
“…During daily practice of meditation by concentrating, on breathing the basic activity of bulbopontine complex is modified in such a way as to slow down its rhythm by voluntarily prolonging the phases of inspiration and expiration by stretching to Ray et al [14] observed significant improvement in VO 2 max after Yogic training. Raju et al [15] have found a significant increase in oxygen consumption per unit work after yoga training which are similar to our study. Improvement in lung functions as well as cellular machinery explains raised VO 2 max after regular practice of meditation.…”
Section: Discussionsupporting
confidence: 92%
“…Yoga postures are performed in a relaxed manner (Kerr, 2000) and sequenced to emphasize balance between strength and flexibility (Brust, 1993). Research indicates that yoga practice is associated with improvements in overall physical fitness (Cowen and Adams, 2005;Tran et al, 2001), along with increases in muscular strength, endurance, and flexibility (Raju et al, 1997;Telles et al, 1993;Tran et al, 2001). Research also supports the belief that yoga is beneficial in reducing perceived stress (Berger and Owen, 1988;Cowen and Adams, 2005) and improving physiological measures of stress (Murugesan et al, 2000;Telles et al, 1993).…”
Section: Introductionmentioning
confidence: 94%
“…Cardiovascular reactivity to stress, a factor strongly associated with insulin resistance 148,149 is also a major independent predictor of hypertension, stroke, myocardial infarction, and cardiovascular mortality 31 ; cardiovascular recovery from stress is a marker of vagal rebound that has likewise been strongly associated with CVD risk. 150 Documented changes associated with the practice of yoga and yoga-based programs in the 7 eligible studies identified include: (1) significantly reduced blood pressure and heart rate responses to stress relative to baseline 105,151 or controls receiving nonyogic exercise, 112 usual care, 152 or no intervention 127,153 ; and (2) accelerated cardiovascular recovery time from stress compared with nonyoga resting poses 144 or controls receiving usual care 152 or no intervention. 153 Finally, 7 recent studies in Indian 111,115,120,140 and European 36,114 populations suggest that participating in yoga and yoga-based programs can improve heart rate variability and baroreflex sensitivity in both healthy 36,111,114,115,140,143 and hypertensive populations 120 (Table 8).…”
Section: Effects Of Yoga On Markers Of Sympathetic/parasympathetic Acmentioning
confidence: 99%